I think the answer is y=2(17)+1.25.
Answer:
$2+$1.25x=$17
Step-by-step explanation:
You have to add the $2 to the $1.25 for each mile then multiply that by x to get $17. I think but I could be wrong
Hello,
All the numbers must begin with 6.
There are still 2,3,4,5 digits : 4 possibilities.
4!=4*3*2*1=24
The first is 62345 and the last 65432.
To find the number of odd numbers greater than 60000 that can be formed using the given numbers with each digit used only once, you can determine the number of possibilities for each digit and multiply them together. The answer is 96.
To find the number of odd numbers greater than 60000 that can be formed using the numbers 2, 3, 4, 5, and 6 with each digit used only once, we need to consider the possible arrangements of these digits. First, we can determine the number of possibilities for the leftmost digit, which must be either 3, 4, 5, or 6. Next, we can determine the number of possibilities for the remaining four digits, which can be arranged in 4! (4 factorial) ways. Multiplying these two values gives us the total number of odd numbers greater than 60000 that can be formed using these digits with each digit used only once.
Thus, the number of odd numbers greater than 60000 that can be formed using the numbers 2, 3, 4, 5, and 6 with each digit used only once is 4 * 4! = 4 * 4 * 3 * 2 * 1 = 96.
#SPJ2
Answer:
ANSWER
x = { - 20}{7}
y={ 4}{7}
Step-by-step explanation:
Answer:
the answer is -6, 2
Step-by-step explanation:
Answer:
the answer is -6, 2
Step-by-step explanation:
Answer: 11 am
hope this helps!
b. x^3
c.x^3+x^2+x+1
d. x^3-2
Answer:
Option C.
Step-by-step explanation:
We have to solve by synthetic division and tell the quotient.
First we will write the numerator in the standard form as
Which will become as
Since denominator of the fraction is (x -1) therefore we take x = 1 as zero root.
Now we form the synthetic form as below
1 0 0 0 -1
1 1 1 1 1 0
x³ x² x
Here coefficient of x³ is 1, for x² is 1, for x is 1, and constant term 1.
Now the fraction will come in the form of
Therefore quotient will be
Option C. is the answer
The mean net worth is $1,000,000, and the median net worth is $87,000,000,000.
After Bill Gates moves into Centerville, the number of people in the town remains the same at 86,999, but the total net worth changes due to his massive wealth.
Mean Net Worth:
To calculate the mean net worth, we divide the total net worth by the number of people. The total net worth is the sum of the net worth of all individuals in Centerville.
Total Net Worth = Net Worth of 86,999 people + Net Worth of Bill Gates
Total Net Worth = 86,999 * 0 + $87,000,000,000 (Bill Gates' net worth)
Mean Net Worth = (Total Net Worth) / (Number of People)
Mean Net Worth = ($87,000,000,000) / (86,999 + 1) [Adding 1 for Bill Gates]
Median Net Worth:
The median net worth is the net worth of the middle person in the sorted list of net worth values. Since we have one extremely wealthy individual (Bill Gates) with a net worth of $87,000,000,000, he becomes the median net worth, as there are an odd number of people in Centerville.
So, after Bill Gates moves into Centerville:
Mean Net Worth = $87,000,000,000 / 87,000 = $1,000,000
Median Net Worth = $87,000,000,000
Therefore, the mean net worth is $1,000,000, and the median net worth is $87,000,000,000.
To know more about net worth:
#SPJ2
I'm assuming you need to find the solution to this system of equations (where the lines intersect).
We can use the substitution method to solve this system. Take the value of from the second equation and substitute it into the first:
Add to both sides of the new equation:
Now add to both sides of the equation:
Divide both sides by :
Now let's solve for by substituting the known value of into the first equation:
Simplify using subtraction:
This means our solution is:
Answer:
x = 3, y = 1
Step-by-step explanation:
Solve the following system:
{y = x - 2 | (equation 1)
y = 7 - 2 x | (equation 2)
Express the system in standard form:
{-x + y = -2 | (equation 1)
2 x + y = 7 | (equation 2)
Swap equation 1 with equation 2:
{2 x + y = 7 | (equation 1)
-x + y = -2 | (equation 2)
Add 1/2 × (equation 1) to equation 2:
{2 x + y = 7 | (equation 1)
0 x+(3 y)/2 = 3/2 | (equation 2)
Multiply equation 2 by 2/3:
{2 x + y = 7 | (equation 1)
0 x+y = 1 | (equation 2)
Subtract equation 2 from equation 1:
{2 x+0 y = 6 | (equation 1)
0 x+y = 1 | (equation 2)
Divide equation 1 by 2:
{x+0 y = 3 | (equation 1)
0 x+y = 1 | (equation 2)
Collect results:
Answer: {x = 3, y = 1